1990
DOI: 10.1021/bi00503a005
|View full text |Cite
|
Sign up to set email alerts
|

Binding of p-nitrophenyl-.alpha.-D-galactopyranoside to lac permease of Escherichia coli

Abstract: Registry No. d(AC)4-d(GT)4, 81609-64-5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 25 publications
3
20
0
Order By: Relevance
“…Scatchard analysis of TDG enhancement of MIANS-labeled W33C permease fluorescence reveals a single binding site with an apparent K O of 71 NM, which coincides with the high-affinity site described previously (Lolkema & Walz, 1990;Lolkema et al, 1991;van Iwaarden et al, 1993;Wu et al, 1995b). Therefore, it appears that occupancy of a high-affinity site in lactose permease causes position 33 to move into a more hydrophobic environment that is less accessible to MIANS, and positions 28 and 3 1 to move into a more hydrophilic environment that is more accessible to the probe.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Scatchard analysis of TDG enhancement of MIANS-labeled W33C permease fluorescence reveals a single binding site with an apparent K O of 71 NM, which coincides with the high-affinity site described previously (Lolkema & Walz, 1990;Lolkema et al, 1991;van Iwaarden et al, 1993;Wu et al, 1995b). Therefore, it appears that occupancy of a high-affinity site in lactose permease causes position 33 to move into a more hydrophobic environment that is less accessible to MIANS, and positions 28 and 3 1 to move into a more hydrophilic environment that is more accessible to the probe.…”
Section: Discussionsupporting
confidence: 83%
“…The fluorescence of MIANS-labeled W33C permease (0.75 pM) was measured as described above, and bound TDG was calculated from the fluorescence increase measured at given TDG concentrations. It was assumed that at saturation one mol of TDG is bound per mol of permease (Lolkema & Walz, 1990). …”
Section: Ligand Bindingmentioning
confidence: 99%
“…Kinetic measurements, binding and site-directed labeling studies indicate that lac permease has two binding sites (13,14,(27)(28)(29). The site-directed fluorescence studies reported here demonstrate that mutants E126A͞V331C, R144A͞V331C, or R144K͞V331C are defective in both sites.…”
Section: Figmentioning
confidence: 49%
“…Binding studies and nonequilibrium exchange measurements have revealed two distinct binding sites per lac permease molecule (monomer) for NPG and lactose (Lolkema & Walz, 1990;Lolkema et al, 1991). The findings that two kinetic phases are observed with respect to external lactose during exchange but only one phase with respect to internal lactose suggest that one site is located on the periplasmic aspect of the permease.…”
Section: Discussionmentioning
confidence: 99%